Ternary content addressable memory for longest prefix matching based on random access memory on field programmable gate array - Ng Shao Kay; M. N. Marsono (Universitas Ahmad Dahlan, 2019)
Conventional ternary content addressable memory (TCAM) provides access to stored data, which consists of '0', '1' and ‘don't care’, and outputs the matched address. Content lookup in TCAM can be done in a single cycle, which makes it very important in applications such as address lookup and deep-packet inspection. This paper proposes an improved TCAM architecture with fast update functionality. To support longest prefix matching (LPM), LPM logic are needed to the proposed TCAM. The latency of the proposed LPM logic is dependent on the number of matching addresses in address prefix comparison. In order to improve the throughput, parallel LPM logic is added to improve the throughput by 10× compared to the one without. Although with resource overhead, the cost of throughput per bit is less as compared to the one without parallel LPM logic.